Balancing Fraud Prevention and Electoral Participation: Attitudes Toward Voter Identification1. (22nd August 2014) - Atkeson, Lonna Rae; Alvarez, R. Michael; Hall, Thad E.; Sinclair, J. Andrew
<x xml:space="preserve">Abstract</x> Objective This article examines public opinion on the effectiveness and consequences of voter identification laws, focusing on the core issue in the Supreme Court's reasoning in the 2008 case that upheld an Indiana photo‐ID law, Crawford v. Marion County Election Board. Method We use a unique survey from New Mexico, where voter identification policies have recently undergone important changes. Questions in the survey examine whether voters think that ID laws protect against fraud and prevent legitimate participation, which point of view voters find more compelling, and whether attitudes toward voter identification are related to voter confidence. Results Most voters think that voter ID laws prevent fraud, but many voters think that ensuring access to the polls is more important than preventing fraud. Among other variables that explain differences among individuals, partisanship plays an important role. Conclusion The framing of voter identification policies plays an important role in how such laws are interpreted by the public and Republicans are especially concerned about fraud in elections.